2020
DOI: 10.1002/ece3.6799
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA analysis reveals spatial genetic structure and high genetic diversity of Massicus raddei (Blessig) (Coleoptera: Cerambycidae) in China

Abstract: The oak longhorned beetle (OLB), Massicus raddei (Blessig, 1872) (Coleoptera: Cerambycidae), is widely distributed in Asia (China, the Korean Peninsula, Japan, Vietnam and the Russian Far‐East), but pest outbreaks have occurred only in Liaoning Province and Jilin Province of China. In order to explore possible mechanisms of local population outbreaks and characterize the genetic diversity and genetic structure of M. raddei across its range in China, three mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
5
2
Order By: Relevance
“…The haplotype network result of Korea RLB showed a moderate star-like topology that many minor haplotypes are related to a major central haplotype. In comparison to our result that the major haplogroup and major haplotype (HG1) are observed in most of the sampled locality, both studies [17,28] rather showed all the sampled populations showed a lack of shared haplotypes. The ubiquitous distribution of major haplogroups (HG1), geographically separated two minor haplogroups (HG2 and HG3), and the moderate overall genetic structure indicates RLB populations in Korea might not be influenced by strong anthropogenic events.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The haplotype network result of Korea RLB showed a moderate star-like topology that many minor haplotypes are related to a major central haplotype. In comparison to our result that the major haplogroup and major haplotype (HG1) are observed in most of the sampled locality, both studies [17,28] rather showed all the sampled populations showed a lack of shared haplotypes. The ubiquitous distribution of major haplogroups (HG1), geographically separated two minor haplogroups (HG2 and HG3), and the moderate overall genetic structure indicates RLB populations in Korea might not be influenced by strong anthropogenic events.…”
Section: Resultscontrasting
confidence: 99%
“…Despite population genetic structure can differ by species [26], sampling [27], and the selected genetic marker [28], our result was different from those of the two closely related species that shows nonstar-like network topology: Chinese Neocerambyx raddei Blessig, 1872 [28], Korean and global Anoplophora glabripennis (Motschulsky, 1854) [17]. The haplotype network result of Korea RLB showed a moderate star-like topology that many minor haplotypes are related to a major central haplotype.…”
Section: Resultscontrasting
confidence: 66%
“…Population genetics can also help reconstruct the demographic history and understand whether a population is native or invasive ( Zheng et al, 2013 ; Men et al, 2017 ). Population genetics also helps determine whether an invasion was the result of multiple independent introduction events or a long-term spread from a single source population ( Xun et al, 2016 ; Zhang et al, 2020 ; Du et al, 2021 ). In this case, genetic polymorphisms transmitted in a strictly Mendelian manner provide useful information.…”
Section: Introductionmentioning
confidence: 99%
“…Massicus raddei is widely distributed in eastern Asia, but only the oak forests of Liaoning and Jilin Provinces in China are severely infested. Sun [ 2 ] and Zhang et al [ 19 , 47 ] both concluded that regional outbreaks of M. raddei in northeastern China could be facilitated by the combined effects of particular periodical emergence behavior and the extensive distribution of susceptible host species. Hence, the present study specifically identified the current distribution and projected the potential distribution of the two susceptible hosts.…”
Section: Discussionmentioning
confidence: 99%